Recurrent new-onset uveitis in a patient with rheumatoid arthritis during anti-TNFα treatment - C. Leonetti; R. Leonardi; R. Foti; M. Di Gangi; P. Castellino (PAGEPress Publications, 2011)
Inflammation involving the uveal tract of the eye, termed uveitis, is frequently associated with various rheumatic disease, including seronegative spondylarthropathies, juvenile rheumatoid arthritis, Crohn's disease and Behçet's disease. Scleritis and keratitis may be associated with rheumatoid arthritis and systemic vasculitides such as Wegener's granulomatosis. Immune-mediated uveitis can have a chronic relapsing course and produce numerous possible complications, many of which can result in permanent vision loss. Treatment typically includes topical or systemic corticosteroids with cycloplegic-mydriatic drugs and/or noncorticosteroid immunosuppressants, but often there is an insufficient clinical effectiveness. Anti-TNFα therapy is promising in the treatment of sight threatening uveitis, particularly in patients with Behçet's disease. However, there have been also reports of new-onset uveitis during treatment of joint disease with TNFα inhibitors. We describe a case of new-onset uveitis in a patient with rheumatoid arthritis during therapy with etanercept at first and infliximab at last. Although we cannot exclude uveitis as linked to rheumatoid arthritis, it is unlike that the uveitis arises when the joint disease is well controlled. The hypothetical paradoxical effect of anti-TNF is here discussed.